Developing numeracy module based on local culture in Indonesia - Muliana Muliana; Hayatun Nufus; Nuraina Nuraina; Nur Mahyuni; Asmaul Husna (Universitas Hamzanwadi, 2023)
Using the numeracy module helps students learn mathematics by providing learning content and improving their motivation. However, it was found that only a few researches were conducted to develop a module designed based on local cultures, like Aceh culture. This study aimed to develop a module based on Aceh culture that supported numeracy. The design of this study was based on a research and development procedure in which the developed module has gone through the stages of analysis, design, development, implementation, and evaluation. The Likert scale type of questionnaire was used as it was very effective in analyzing and gathering views from language and media experts and students. The results indicated that the integration of local culture in elementary school students’ modules was evaluated to be valid by teaching module experts in terms of media, materials, and language. In addition, the developed-local culture module was regarded as feasible and effective, identified from students’ views as having average scores of 3.58 or 89.77 %. The feasibility and the effectiveness of the elementary school’s literacy and numeracy module based on local culture were very appropriate to be applied in the classroom.